Foucault’s Method as Subjectification and Developing of an Immanent Life Review of the book Genealogy is Gray: Reflections on Foucault’s Method - Meysam Ghahreman (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The main concern of this paper is to counter the ruling rationality of the humanities, which makes writings and classrooms of “Riskless and timely Foucault”. The rationality that has appropriated Foucault to reproduce the student-teacher relationship and write treatises and scientific books. According to this rationality, first, Foucault is Periodize, and then these periods are taught by a professor who, as a subject, is confronted with Foucault’s object and strictly observes the method of scientific references while truth Foucault (Truth does not mean the exact references of the subject to the object of Foucault’s works) is an untimely Foucault that develops an immanent life in the present. Therefore, in order to counter the academic Foucault, it is necessary to provide a reading of the Foucault that has no Periodization (One should not even understand the periods in relation to each other) because these Periodizations make it possible that Foucault can be conquered by the forces of academic rationality. As a result, Foucault’s method should be considered as a subjectification and continuous production of the untimely, whereby the subjugation of knowledge and relations of power are immanent subjects as an immanent life.